A DAG-Based Post-Quantum Ledger - Freitas, Allan Edgard Silva (Anais Estendidos do Latin-American Symposium on Dependable and Secure Computing (LADC), 2025)
Quantum computing threatens foundational cryptographic assumptions in today’s distributed ledgers, while application demands outgrow the throughput and latency ceilings of single-chain blockchains. Directed acyclic graph (DAG) ledgers unlock parallelism but raise new questions about ordering, security, and light-client viability. This position paper argues for a postquantum (PQ) DAG ledger that matches DAG concurrency with PQ-secure consensus and transactions, plus a privacy-preserving identity/reputation layer. We sketch the architecture, situate it against the literature, and enumerate some open challenges to be addressed for deployment at scale. A carefully engineered PQ DAG can provide credible security and performance in a quantum-enabled adversarial landscape.